Sex differences in self-estimation of multiple intelligences among Portuguese adolescents - Felix Neto (2008)
This study investigated the relationship among sex, attitude toward intelligence, and self-estimation of multiple intelligences for self and parents among Portuguese adolescents in secondary schools. Two hundred and forty-two adolescents estimated their own and their parents' IQ scores on each of Gardner's 10 multiple intelligences: verbal (linguistic), logical (mathematical), spatial, musical, body-kinesthetic, interpersonal, intrapersonal, existential, spiritual, and naturalistic. They also answered six simple questions concerning intelligence and intelligence tests. There were various sex differences in self-estimated IQ: males rated themselves higher on overall, mathematical, spatial, intrapersonal, spiritual, and naturalistic IQ compared with females. Multiple regressions indicated that verbal, logical, and intrapersonal intelligence were significant predictors for self and parents overall IQ estimations. Factor analysis of the 10, the 8, and the 7 self-estimates scores did not confirm Gardner's classification of multiple intelligences. Males were more likely to believe in sex differences in intelligence than females. Results are discussed in terms of the growing literature in the self-estimates of intelligence, as well as limitations of that approach.